SiLiF Neutron Counters to Monitor Nuclear Materials in the MICADO Project - Luigi Cosentino; Quentin Ducasse; Martina Giuffrida; Sergio Lo Meo; Fabio Longhitano; Carmelo Marchetta; Antonio Massara; Alfio Pappalardo; Giuseppe Passaro; Salvatore Russo; Paolo Finocchiaro (Sensors, 2021)
In the framework of the MICADO (Measurement and Instrumentation for Cleaning And Decommissioning Operations) European Union (EU) project, aimed at the full digitization of low- and intermediate-level radioactive waste management, a set of 32 solid state thermal neutron detectors named SiLiF has been built and characterized. MICADO encompasses a complete active and passive characterization of the radwaste drums with neutrons and gamma rays, followed by a longer-term monitoring phase. The SiLiF detectors are suitable for the monitoring of nuclear materials and can be used around radioactive waste drums possibly containing small quantities of actinides, as well as around spent fuel casks in interim storage or during transportation. Suitable polyethylene moderators can be exploited to better shape the detector response to the expected neutron spectrum, according to Monte Carlo simulations that were performed. These detectors were extensively tested with an AmBe neutron source, and the results show a quite uniform and reproducible behavior.